Chronic idiopathic urticaria: Prevalence and clinical course - Kanokvalai Kulthanan (2018)
The purpose of our study was to assess the prevalence and clinical course of patients with chronic idiopathic urticaria (CIU), as well as possible causes or associated findings, laboratory findings and the duration of the disease in patients with chronic urticaria (CU). We retrospectively reviewed the 450 case record forms of patients with CU and/or angioedema who attended the Department of Dermatology, Siriraj Hospital, during the period 2000-2004. Of 450 patients with CU, 337 patients (75%) were diagnosed as CIU. Forty-three patients (9.5%) had physical urticaria, while 17 patients (3.8%) had infectious causes. Other possible causes were food, thyroid diseases, atopy, drugs, dyspepsia and collagen vascular diseases. In eighty-nine percent of patients, no abnormalities were detected at the time of physical examination. The most common abnormal laboratory finding was minimal elevation of the erythrocyte sedimentary rate (42%). In 61 patients, autologous serum skin tests had been done. Fifteen patients (24.5%) had positive results i.e. autoimmune urticaria. Anti-thyroglobulin and anti-microsomal antibodies were positive in 16 % and 12% of CIU patients respectively. After 1 year from the onset of the symptoms, 34.5% of CIU patients were free of symptoms and after 1.2 years from the onset of the symptoms, 56.5% of autoimmune urticaria patients were free of symptoms. The median disease duration of CIU and autoimmune urticaria were 390 days and 450 days respectively. Our study provided an overview of CU and CIU in a large series of Thai patients, based on etiological aspects and clinical courses. © 2007 Japanese Dermatological Association.